Hadith #2280 - Sunan Abi Dawud - Amr bin Muhajir bin 'Abi Muslim عمرو بن المهاجر بن أبي مسلم; Asma' bint Yazid bin al-Sakan; Isma'il bin Ayyash bin Saleem إسماعيل بن عياش بن سليم; Muhajir bin Abi Muslim; Yahya bin Salah al-Wahadi يحيى بن صالح الوحاظي أبو زكريا (Sunan Abi Dawud)
When we came out from Mecca, Hamzah’s daughter pursued us crying: My uncle. Ali lifted her and took her by the hand. (Addressing Fatimah he said:) Take your uncle’s daughter. She then lifted her. The narrator then transmitted the rest of the tradition. Ja’far said: She is my uncle’s daughter. Her maternal aunt is my wife. The Prophet (ﷺ) decided in favour of her maternal aunt, and said: The maternal aunt is like mother.
Grade: Sahih

Hadith #3880 - Sunan Abi Dawud - al-Rabi' bin Nafi' Abu Tawba al-Halbi الربيع بن نافع أبو توبة الحلبي; Asma' bint Yazid bin al-Sakan; Muhajir bin Abi Muslim; Muhammad bin Muhajir bin Abi Muslim محمد بن مهاجر (Sunan Abi Dawud)
The man casting evil would be commanded to perform ablution, and then the man affected was washed with it.
Grade: Da'if